Techno-economic modelling of cogeneration options for the South African sugar industry - Masenda, Joseph (Department of Mechanical Engineering, 2022)
Cogeneration is a core part of the SA sugar industry operations. Most factories in SA already cogenerate, but not to their full potential. Improving cogeneration through better energy utilisation than the usual status-quo can potentially enhance profitability. However, investment in cogeneration in the sugar industry is not taking place and although factories have proven to be able to produce excess power, many are not selling it back to the national grid. This research aimed to further the understanding of the SA sugar industry cogeneration options with the use of techno-economic modelling methods over a planning horizon extending to 2040. The methodological approach adopted for the study, configures the industry's cogenerating system, and allowed the adoption of additional options likely to play a role in assisting cogenerating performance in 2025. Some cogenerating technologies that were explored were back-pressure and condensing extraction steam turbines, as well as, high-efficiency gas engines in open and closed cycles. The least-cost optimizing TIMES modelling framework was used to evaluate the cogeneration investment decision for different cogeneration configurations under different scenarios, and to capture some of the uncertainties faced by the industry. Each scenario was evaluated using a set of techno-economic indicators, justifying the viability of technological implementations in cogenerating system pathways. Focusing on these transformative pathways highlighted diversification cogenerating options, whilst simultaneously ensuring the fulfilment of the industry's sugar production obligations, for the domestic as well as foreign market under pressure from competitive forces. Input data for model parameters stemmed from literature and information sources applied to Microsoft excel spreadsheets calculations. Analysed outcomes were scrutinised using tableau, which generated output data from iterating modelled power purchase agreement (PPA) and break-even tariff determinations. The assessment of generated transformative pathways was compared to metrics from other sugar-producing countries, with successfully diversified mills, using evaluated scenarios to emphasize the unit costs per energy in R2015/KWh. Research findings showed cogeneration feasibility at subsidised tariffs of between 1.20 and 1.76 R/kWh for steam turbines and gas turbines in open cycles, with combinedcycling from intergrated bagasse gasification being feasible from 1.20 to 1.37 R/KWh. Feasibly installed CHP technologies were concluded to have potential magnitudes of between 350 up to 800 MWe depending on the scenario.